Implementasi Administrasi dan Supervisi Pendidikan di Madrasah Ibtidayah - Putri Hajiati; Ardian Lestari; Lisa Aulia Zulva; Latifah Khoiriyatul H; Nurranafitria luthfi; Imam Mustopa (Jurnal Ilmu Tarbiyah, 2026)
This study aims to describe the implementation of educational administration and supervision at Madrasah Ibtidayah. The research used a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results show that educational administration, encompassing student management, curriculum, human resources, facilities and infrastructure, budget, and school information systems, has been carried out fairly well. Educational supervision is conducted through guidance, curriculum monitoring, teacher training, and periodic evaluation by the principal. The main obstacles are limited facilities, variations in teachers' ability to implement the curriculum, and the not fully optimized use of the information system. Overall, the implementation of administration and supervision is effective And in education management, it is necessary to improve infrastructure, empower teachers' abilities in implementing the curriculum, and use information systems.